PEMANFAATAN PETA TEMATIK UNTUK ANALISIS POTENSI SOSIAL-EKONOMI DALAM PENGEMBANGAN WILAYAH DESA TANJUNG SANGKAR - Dharma Putri, Vadma; Martahayu, Vika; Iswandi, Ahmad; Mardita, Sasi; Julian, Sevti; Awaliyah, Annisa Nurhafiza; Maulida, Maulida; Haiza, Vivi Fadillah; Sulistia, Hilda; Egil, Egil; Putra, Wahyu Ilham; Alamsyah, Fadli (Yayasan Education and Social Center, 2025)
Tanjung Sangkar Village, located in Lepar Pongok District, South Bangka Regency, has significant economic potential in the fisheries and marine tourism sectors. However, the lack of documentation and territorial mapping poses challenges in managing and promoting the village’s potential. Therefore, this community service initiative, conducted through the Kuliah Kerja Nyata (KKN) Kedisinian programme of Muhammadiyah University of Bangka Belitung (Unmuh Babel), aims to develop a digital thematic map that can serve as a reference for data-driven decision-making. The implementation method includes field surveys, data collection, design phase, map validation, and handover to the village administration. The results of this programme indicate that the thematic map enhances the effectiveness of development planning, economic potential promotion, and community participation in territorial management. In conclusion, the utilisation of digital thematic maps can be a strategic tool in supporting data-based rural development and attracting investment in the tourism and local industry sectors.